Using finite elements in mechanical design - Mottram, James Toby. (McGraw-Hill, 1996)
This book is about: Relationship between design and finite elements; Structural mechanics; Finite element solutions of the equations; Implementing a computer-based analysis procedure; Building the geometry description and the mesh; Obtaining and analysing the results; ..